2022
DOI: 10.1073/pnas.2204084119
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in MINAR2 encoding membrane integral NOTCH2-associated receptor 2 cause deafness in humans and mice

Abstract: Discovery of deafness genes and elucidating their functions have substantially contributed to our understanding of hearing physiology and its pathologies. Here we report on DNA variants in MINAR2 , encoding membrane integral NOTCH2-associated receptor 2, in four families underlying autosomal recessive nonsyndromic deafness. Neurologic evaluation of affected individuals at ages ranging from 4 to 80 y old does not show additional abnormalities. MINAR2 is a recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The degree of hearing loss in mutant minar2 fs139 zebrafish larvae is not as severe as it was in the adult knockout mouse. A recently published study showed that Minar2 knockout mice had degeneration of hair cells and progressive sensorineural hearing loss ( Bademci et al, 2022 ). In mutant minar2 fs139 zebrafish, the reduction of inner ear hair cell numbers is progressive, worsening from no changes in the larval stage to a 30% reduction in the adult stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of hearing loss in mutant minar2 fs139 zebrafish larvae is not as severe as it was in the adult knockout mouse. A recently published study showed that Minar2 knockout mice had degeneration of hair cells and progressive sensorineural hearing loss ( Bademci et al, 2022 ). In mutant minar2 fs139 zebrafish, the reduction of inner ear hair cell numbers is progressive, worsening from no changes in the larval stage to a 30% reduction in the adult stage.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the conserved requirement of Kiaa1024L/Minar2 gene orthologs for hearing in both mice and zebrafish, and that the human ortholog MINAR2 is also specifically expressed by the auditory hair cells ( Steinhart et al, 2022 ), it will be important to examine whether KIAA1024L/MINAR2 gene mutations may underline hearing abnormalities in humans. Indeed, while this study was under review, it was reported that mutations in MINAR2 cause deafness in human patients ( Bademci et al, 2022 ). Further studies of Kiaa1024L/Minar2’s regulation of cholesterol distribution and homeostasis in the zebrafish and mammalian models will provide new insights into the biological processes underlying the morphogenesis and physiology of hair bundles and hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Whole‐genome sequencing was performed as previously reported (Bademci et al, 2022). Briefly, whole‐genome sequencing from proband was performed at the University of Miami Hussman Institute of Human Genetics sequencing core.…”
Section: Methodsmentioning
confidence: 99%
“…Mice, in particular, are the most commonly used and numerous genetically modified mouse strains have been created that mimic various types of human hearing loss, including both non-syndromic and syndromic forms ( Jiang et al, 2023 ). For example, the Minar2 mutation responsible for DFNB120 was confirmed using the mouse models, with mutant mice rapidly developing progressive sensorineural deafness, accompanied by a reduction in outer hair cell stereocilia in the shortest row and degeneration of hair cells at a later age ( Bademci et al, 2022 ). These models have significantly advanced our understanding of the mechanisms underlying hearing loss and provided valuable insights into potential therapeutic strategies for treating human hearing impairment.…”
Section: Introductionmentioning
confidence: 99%